Why are there apes? Evidence for the co‐evolution of ape and monkey ecomorphology. Issue 4 (April 2016) - Hunt, Kevin D.
Abstract: Apes, members of the superfamily Hominoidea, possess a distinctive suite of anatomical and behavioral characters which appear to have evolved relatively late and relatively independently. The timing of paleontological events, extant cercopithecine and hominoid ecomorphology and other evidence suggests that many distinctive ape features evolved to facilitate harvesting ripe fruits among compliant terminal branches in tree edges. Precarious, unpredictably oriented, compliant supports in the canopy periphery require apes to maneuver using suspensory and non‐sterotypical postures (i.e. postures with eccentric limb orientations or extreme joint excursions). Diet differences among extant species, extant species numbers and evidence of cercopithecoid diversification and expansion, in concert with a reciprocal decrease in hominoid species, suggest intense competition between monkeys and apes over the last 20 Ma. It may be that larger body masses allow great apes to succeed in contest competitions for highly desired food items, while the ability of monkeys to digest antifeedant‐rich unripe fruits allows them to win scramble competitions. Evolutionary trends in morphology and inferred ecology suggest that as monkeys evolved to harvest fruit ever earlier in the fruiting cycle they broadened their niche to encompass first more fibrous, tannin‐ and toxin‐rich unripe fruits and later, for some lineages, mature leaves. Early depletion of unripe fruit in the central core of the tree canopy by monkeys leaves a hollow sphere of ripening fruits, displacing antifeedant‐intolerant, later‐arriving apes to small‐diameter, compliant terminal branches. Hylobatids, orangutans, Pan species, gorillas and the New World atelines may have each evolved suspensory behavior independently in response to local competition from an expanding population of monkeys. Genetic evidence of rapid evolution among chimpanzees suggests that adaptations to suspensory behavior, vertical climbing, knuckle‐walking, consumption of terrestrial piths and intercommunity violence had not yet evolved or were still being refined when panins (chimpanzees and bonobos) and hominins diverged.